STRATEGI EMPLOYEE RELATIONS MANAGEMENT DI PT. KEMFARM INDONESIA: Fathiya Nur Rahmi, Hanny Hafiar, Priyo Subekti - Fathiya Nur Rahmi; Hanny Hafiar; Priyo Subekti (Prodi Ilmu Komunikasi Universitas Putera Batam, 2018)
Kemfarm Indonesia is a company engaged in the field of agribusiness knew that employee relationship becomes important thing for the progress of the company. This study aims to determine the process of employee relationship management in PT Kemfarm Indonesia. The method used is descriptive with qualitative data. The research data was collected by observation, structured interview and literature study. The results show that HRD PT Kemfarm Indonesia acts as an internal PR managed relationships between companies, from processes, organizing, monitoring, evaluation and development program. In the process of planning, organizing, and program evaluation, the communications channel has not been optimal. From the results of this study, the suggestions provided are companies that do mapping the situation specifically on the process of planning, organizing and evaluation by using an effective communication channel on every program implementation so that the main goal of the program can be achieved.